Hadith-hadith daif dan palsu dalam Nasa’ih al-‘Ibad oleh Nawawi Banten: Pengaruhnya terhadap masyarakat Islam di Sumatera / Arwansyah Kirin - Arwansyah, Kirin (2016)
The book of “Na‘i al-‘Ibd” by Shaykh Nawaw al Batan is a tasawuf which contained various categories of hadith. Therefore, it should be studied on its legitimacy where it has been made as public referral widely among the community, especially the Ma’had in Indonesia. The set of problems that derived within this scripture are the status of the hadith, mostly have not been takhrj and legally authenticated. Hence, the researchers had to perform the takhrj of these hadith in this scripture beginning from chapter five until chapter ten. They (the researchers) ought to clarify the status and the source of the hadith, whether it is a, a’f or Maw’ dependable on the ulama (which specialized in Hadith) point of view, and also how it has influenced the Islamic community in Sumatera, Indonesia. The objective of the research is to determine the strengths or the weaknesses of each hadith in the Na’i al-‘Ibd scripture, together on how it has impacted and influenced the weak (a’f) and fabricated (Maw’) Hadith among the Islamic community in Sumatera, Indonesia. The methodology that has been used, is to analyze the content of document base on the volume of hadith, whether, it is matan or sanad, together with the interrogation methodology. Whereas, in a data analysis, researchers are currently using the inductive method. Of the 236 hadith texts that have been analyzed, it was found that there are 49 authentic ahadith, 13 fine ahadith, 68 weak ahadith, 20 are the weakest ahadith, 66 fabricated ahadith, and 20 came from unknown sources. An analysis on a research being forwarded to 210 respondents, and the researchers have found that, 54.48 % of those respondents knew the meaning of the hadith. 49.52 % of the respondents are practicing ahadith weak and fabricated, which has been studied. In understanding the hadith status point of view, 44.81 % of the respondents, are not knowing the details of the hadith. The sense of eagerness to disseminate the hadith is not encouraging within the respondents, which is merely 57.38 %. On the implementation of the hadith, it is found that 75.28 % of the respondents had never disseminate it (the hadith) to other people.